Status of islet transplantation and innovations to sustainable outcomes: novel sites, cell sources, and drug delivery strategies - Wong, Jordan M.; Pepper, Andrew R. (Frontiers in Transplantation, 2024)
Islet transplantation (ITx) is an effective means to restore physiologic glycemic regulation in those living with type 1 diabetes; however, there are a handful of barriers that prevent the broad application of this functionally curative procedure. The restricted cell supply, requisite for life-long toxic immunosuppression, and significant immediate and gradual graft attrition limits the procedure to only those living with brittle diabetes. While intraportal ITx is the primary clinical site, portal vein-specific factors including low oxygen tension and the instant blood-mediated inflammatory reaction are detrimental to initial engraftment and long-term function. These factors among others prevent the procedure from granting recipients long-term insulin independence. Herein, we provide an overview of the status and limitations of ITx, and novel innovations that address the shortcomings presented. Despite the marked progress highlighted in the review from as early as the initial islet tissue transplantation in 1893, ongoing efforts to improve the procedure efficacy and success are also explored. Progress in identifying unlimited cell sources, more favourable transplant sites, and novel drug delivery strategies all work to broaden ITx application and reduce adverse outcomes. Exploring combination of these approaches may uncover synergies that can further advance the field of ITx in providing sustainable functional cures. Finally, the potential of biomaterial strategies to facilitate immune evasion and local immune modulation are featured and may underpin successful application in alternative transplant sites.